(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the usefulness of Bronchoscopy Technique in the diagnosis of unsuspected pulmonary disease presenting with Hamoptysis. Study Design: Case serious study. Place and Duration of Study: This study was carried out at the pulmonology Unit of Postgraduate Medical Institute Lady Reading Hospital, Peshawar, Khyber Pakhtunkhwa from 15-04-2011 to 15-04-2012. Material and Method: Two hundred and fifty male smoker patients with age limit of 40-70 years presenting with hemoptysis having clinical suspension of unsuspected pulmonary disease and fulfilling the inclusion criteria underwent bronchoscopy. The bronchoscopic finding and demographic information were determined regarding their frequencies and percentage. Result: Frequency distribution of pulmonary Tuberculosis 94.59% in age range 40-50 years and 5.4% in 51-60 years. Bronchietasis 88.3% 50-60 years and 11.6% in 61-70 years. Chronic Bronchitis with respect to age range of 27.58% in the age range 40-50 years 72.43% in age 51-60 years. Conclusion: Branchoscopy Techniques is a very useful for the determination of unsuspected cases of pulmonary diseases.